Christian Punk : identity and performance. ([London, England] : Bloomsbury Academic, 2020)
"Christian punk is a surprisingly successful musical subculture and a fascinating expression of American evangelicalism. Situating Christian punk within the modern history of Christianity and the rapidly changing culture of spirituality and secularity, this book illustrates how Christian punk continues punk's autonomous and oppositional creative practices, but from within a typically traditional evangelical morality. Analyzing straight edge Christian abstinence and punk-friendly churches, this book also focuses on gender performance within a subculture dominated by young men in a time of contested gender roles and ideologies. Critically-minded and rich in ethnographic data and insider perspectives, Christian Punk will engage scholars of contemporary evangelicalism, religion and popular music, and punk and all its related subcultures."--
List of Figures -- Contributors -- Acknowledgements -- Introduction: Studying Christian Punk, Ibrahim Abraham (Australian National University) 1. Rebel with a Cross: The Development of an American Christian Youth Culture, Eileen Luhr (California State University, Long Beach) 2. "We're Not into Social Compliance': Sin and Prophetic Protest in Christian Punk, Eric Strother (Anderson University) 3. Fearless Men of God: Fighting Religious Stigma in Hardcore Punk, Amy D. McDowell (University of Mississippi) 4. Straight Edge Evangelicalism and DIY Spirituality, Ibrahim Abraham (Australian National University) and Francis Stewart (Bishop Grosseteste University) 5. "Grow a Beard and Be Somebody': Disavowal and Vector Space at Rocketown, Nashville, Joshua Kalin Busman (University of North Carolina at Pembroke) 6. "A Heterosexual Male Backlash': Punk Rock Christianity and Missional Living at Mars Hill Church, Seattle, Maren Haynes Marchesini (Carroll College) 7. Todd and Becky: Authenticity, Dissent, and Gender in Christian Punk and Metal, Nathan Myrick (Mercer University) 8. "Lift Each Other Up': Punk, Politics, and Secularization at Christian Festivals, Andrew Mall (Northeastern University) 9. Christian Punk in (Post)secular Perspectives, Ibrahim Abraham (Australian National University) 10. Blasphemy, Conversion, and Liberation: "Christian" "Punk" in Theological Perspective, Michael J. Iafrate (University of Toronto) Conclusion: Performing Christian Punk Identity, Ibrahim Abraham (Australian National University) References Index.
Includes bibliographical references and index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: Rock music -- Religious aspects -- Christianity; Punk culture; Other Nonconformist & Evangelical Churches; Electronic books